Mesoporous carbon supported PtRu as anode catalyst for direct methanol fuel cell: Polarization measurements and electrochemical impedance analysis of mass transport - Bruno, Mariano Martin; Petrucelli, M. Agustina; Viva, Federico Andres; Corti, Horacio Roberto (Elsevier, 2013)
Fil: Bruno, Mariano Martin. Comisión Nacional de Energía Atómica. Gerencia del Area de Investigaciones y Aplicaciones No Nucleares. Gerencia de Física (Centro Atómico Constituyentes); Argentina. Universidad Nacional de San Martín. Escuela de Ciencia y Tecnología; Argentina